2016
DOI: 10.23937/2469-5726/1510029
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Effect of Antioxidant Pequi (Caryocar Brasiliense) Oil Capsules and Antioxidant Effect of Vitamin D and Physical Activity on Systemic Lupus Erythematosus Patients

Abstract: Objectives: Verifying in SLE patients whether antioxidant supplementation with pequi oil capsules could reduce oxidative DNA damage and inflammation in SLE patients. Patients and Methods:A controlled randomized, crossover, double-blind study was conducted with 38 SLE patients aged 18 to 60, with SLE Disease Activity Index (SLEDAI) below 10, chosen from 73 lupus patients consecutively seen in the University Hospital of Brasília (HUB) Rheumatology Clinic. They were randomized into two groups: one group of 22 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 57 publications
1
9
1
1
Order By: Relevance
“…Furthermore, there was a tendency for blood pressure reduction, suggesting a possible hypotensive effect of the supplementation. In addition, previous investigations using the same dosage of the present study showed that pequi supplementation for 14 days may also attenuate DNA damage in runners , as well as diminish inflammation measured by high sensitive C-reactive protein in a sample of chronic inflammatory disease patients after 60 days of intervention (MONTALVÃO et al, 2016). In an animal model, a previous study showed that pequi oil supplementation for 5 weeks promoted a protective effect on the hepatic tissue by reducing lipid peroxidation after swimming exercise (VALE et al, 2019).…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, there was a tendency for blood pressure reduction, suggesting a possible hypotensive effect of the supplementation. In addition, previous investigations using the same dosage of the present study showed that pequi supplementation for 14 days may also attenuate DNA damage in runners , as well as diminish inflammation measured by high sensitive C-reactive protein in a sample of chronic inflammatory disease patients after 60 days of intervention (MONTALVÃO et al, 2016). In an animal model, a previous study showed that pequi oil supplementation for 5 weeks promoted a protective effect on the hepatic tissue by reducing lipid peroxidation after swimming exercise (VALE et al, 2019).…”
Section: Discussionsupporting
confidence: 63%
“…Of note, findings of previous research showed that supplementation with pequi oil (i.e. 400mg/day) can attenuate cardiovascular inflammation in Systemic lupus erythematosus patients [2]. Moreover, it has been shown that pequi oil supplementation (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…Studies have shown that the ethanol extract of this fruit has high total phenolic content and an excellent antioxidant activity via bioactive molecules (Miranda-Vilela et al, 2009a). Montalvão et al (2016) studying the antioxidant effect of pequi oil in patients with systemic lupus erythematosus have shown a significant reduction of the inflammatory processes. However, no consistent data were found about the possible protective role of the antioxidants contained in pequi oil during strenuous exercise, in terms of maintaining the morphological integrity of liver cells, justifying our study.…”
Section: Introductionmentioning
confidence: 99%